Global curriculum in surgical oncology. Issue 6 (June 2016) - Are, C.; Berman, R.S.; Wyld, L.; Cummings, C.; Lecoq, C.; Audisio, R.A.
Abstract: Background: The significant global variations in surgical oncology training paradigms can have a detrimental effect on tackling the rising global cancer burden. While some variations in training are essential to account for the differences in types of cancer and biology, the fundamental principles of providing care to a cancer patient remain the same. The development of a global curriculum in surgical oncology with incorporated essential standards could be very useful in building an adequately trained surgical oncology workforce, which in turn could help in tackling the rising global cancer burden. Materials and methods: The leaders of the Society of Surgical Oncology and European Society of Surgical Oncology convened a global curriculum committee to develop a global curriculum in surgical oncology. Results: A global curriculum in surgical oncology was developed to incorporate the required domains considered to be essential in training a surgical oncologist. The curriculum was constructed in a modular fashion to permit flexibility to suit the needs of the different regions of the world. Similarly, recognizing the various sociocultural, financial and cultural influences across the world, the proposed curriculum is aspirational and not mandatory in intent. Conclusions: A global curriculum was developed which may be considered as a foundational scaffolding for training surgical oncologists worldwide. It is envisioned that this initial global curriculum will provide a flexible and modular scaffolding that can be tailored by individual countries or regions to train surgical oncologists in a way that is appropriate for practice in their local environment. Abstract : The proposed global curriculum – developed by the Society of Surgical Oncology and the European Society of Surgical Oncology – is proposed to address the variations and streamline global surgical oncology education to help in tackling the rising global cancer burden.